2019
DOI: 10.3390/jfmk4030065
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometer-Based Physical Activity Levels Differ between Week and Weekend Days in British Preschool Children

Abstract: Participation in physical activity (PA) is fundamental to children’s future health. Studies examining the temporal pattern of PA between weekdays and weekends in British preschool children are lacking. Therefore, the aim of this study was to compare PA levels between week and weekend days for UK preschool children, using objective measurements. One hundred and eighty-five preschool children (99 boys, 86 girls, aged 4–5 years), from central England wore a triaxial accelerometer (GENEActiv) for 4 days to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 61 publications
0
9
1
Order By: Relevance
“…Furthermore, the sampling strategy may have attracted participants with parents who promote their PA, motor-skill development and school readiness beyond the typical parent, potentially making the sample unrepresentative. This may explain why MVPA in this study (99.6 ± 23.6 min/day) was higher than previously reported [49,50] and a larger percentage of children in the sample achieved school readiness than the national average (79.6% in this sample compared to 71.8% in England) [7]. Another limitation of this study is the use of accelerometers to assess PA, which does not accurately assess activities such as cycling and is removed for water-based activities, so may underestimate habitual PA levels.…”
Section: Strengths and Limitationscontrasting
confidence: 79%
“…Furthermore, the sampling strategy may have attracted participants with parents who promote their PA, motor-skill development and school readiness beyond the typical parent, potentially making the sample unrepresentative. This may explain why MVPA in this study (99.6 ± 23.6 min/day) was higher than previously reported [49,50] and a larger percentage of children in the sample achieved school readiness than the national average (79.6% in this sample compared to 71.8% in England) [7]. Another limitation of this study is the use of accelerometers to assess PA, which does not accurately assess activities such as cycling and is removed for water-based activities, so may underestimate habitual PA levels.…”
Section: Strengths and Limitationscontrasting
confidence: 79%
“…Furthermore, parents need to be aware of their important role as PA models. This study and several others [20,84] revealed that at weekends young children present low PA levels, with the vast majority (97%) spending their time on sedentary behaviors [20,85]. Taking into consideration that, at the weekends, young children share their leisure-time with their parents, this finding shows the negative influence of parents on their offspring's PA and thus calls for action.…”
Section: Discussionmentioning
confidence: 48%
“…It has been recommended that preschool children in the UK should be participating in at least 180 min of PA per day and this should include 60 min of moderate to vigorous PA (MVPA) [5]. Unfortunately, preschool children spend the majority of their day in SB and a low proportion of their day in MVPA (<15%) [6][7][8][9][10][11][12] with only one in 10 children meeting the recommendations of at least 180 min of PA per day in England [13].…”
Section: Introductionmentioning
confidence: 99%
“…It is of interest to determine how preschool children's PA is accrued during the weekdays, when they attend preschool, in the weekend days, when they are influenced by their home environment and when combining weekend and weekdays. Indeed, weekday vs. weekend PA levels have routinely been reported to vary [19,[21][22][23], with studies from Australia and England suggesting that preschool children are more physically active on weekend days [23,24], and others reporting greater MVPA engagement during the weekdays in Sweden, Denmark, England and Finland [11,19,22,25,26]. Therefore, with these discrepancies, vital additional research is required to identify any differences in PA levels and SB between weekdays, weekend days and four-day combinations in preschool children, considering the influence of FMS concurrently.…”
Section: Introductionmentioning
confidence: 99%